Enrichment of hydroxylated C24- and C26-acyl-chain sphingolipids mediates PIN2 apical sorting at trans-Golgi network subdomains - Valérie Wattelet-Boyer (Nature Portfolio, 2016)
Sphingolipids in the trans-Golgi network have been implicated in polar trafficking. Here Wattelet-Boyer et al. show that hydroxylated C24- and C26-acyl-chain sphingolipids are enriched in trans-Golgi network subdomains that are critical for polar sorting of the PIN2 auxin carrier in plant cells.